Detection of Mitotic Cells in Histopathological Images Using Textural Features - Albayrak, Abdulkadir; Bilgin, Gokhan (IEEE, 2013)
In this work, segmentation of cellular structures in the high resolutional histopathological images and possibility of the discrimination within normal and mitotic cells has been investigated. Mitosis detection is very exhaustive and time consuming process. In the first step, features of cells which have been found by the clustering algorithm have been extracted by oriented gradient histograms (HOG) method which is known as a robust texture descriptor. A mitotic cell has some textural changes that makes it recognizable among other normal cells. Hence, the classification accuracy of the unsupervised learning methods is increased after making use of proposed textural descriptor.
Keywords: Histopathological images; mitosis detection; histogram of oriented gradients; segmentation; classification; TRACKING; Engineering; Telecommunications